2008
DOI: 10.1200/jco.2007.12.0733
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Dose-Dense Doxorubicin and Cyclophosphamide Followed by Paclitaxel With Trastuzumab in HER-2/neu Overexpressed/Amplified Breast Cancer

Abstract: Dose-dense AC followed by P/T followed by T is feasible and is not likely to increase the incidence of cardiac events compared to established regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…Subsequently, we demonstrated that ddAC followed by paclitaxel (P) with T was associated with an overall CHF rate of 1.4% (1/70 patients; ref. 6). Taken together, these findings suggest that dd anthracycline-based chemotherapy incorporating T is associated with a low risk of cardiotoxicity.…”
Section: Introductionmentioning
confidence: 75%
“…Subsequently, we demonstrated that ddAC followed by paclitaxel (P) with T was associated with an overall CHF rate of 1.4% (1/70 patients; ref. 6). Taken together, these findings suggest that dd anthracycline-based chemotherapy incorporating T is associated with a low risk of cardiotoxicity.…”
Section: Introductionmentioning
confidence: 75%
“…Combining dose-dense AC and paclitaxel with HER2-targeted therapy appears to be safe from a cardiac point of view, and toxicity does not seem to be increased in relation to previous non-dose-dense HER2 clinical trials [32,33,34]. This makes sense if we consider that no trial has shown increased cardiac risk with reduced anthracycline intervals [21,22,25,28].…”
Section: Special Populations and Final Remarksmentioning
confidence: 98%
“…In this trial, a significant benefit was found for the dose-dense group. Based upon those results and confirmatory data [33,34], dose-dense regimens are today deemed standard in North America. Likely independent of G-CSF support, a just recently observed potential drawback of dosedense treatment is a decline in pulmonary function, as defined by a significant reduction of carbon monoxide diffusion capacity [35].…”
Section: Studies Of G-csf In Breast Cancermentioning
confidence: 87%